2022
DOI: 10.1093/cercor/bhab517
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitable and immature-like neuronal activity in the auditory cortex of adult rats lacking the language-linked CNTNAP2 gene

Abstract: The contactin-associated protein-like 2 gene, CNTNAP2, is a highly penetrant risk gene thought to play a role in the genetic etiology of language-related disorders, such as autism spectrum disorder and developmental language disorder. Despite its candidacy for influencing language development, few preclinical studies have examined the role of CNTNAP2 in auditory processing. Using in vivo and in vitro electrophysiological recordings in a rat model with translational validity, we report that a loss of the Cntnap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 70 publications
2
17
1
Order By: Relevance
“…A higher frequency of mEPSPs than mIPSPs compared to WTs has been observed in A1 of VPA mice, Ehmt1 +/− mice and Pten conditional knockout mice, indicating underlying hypersensitivity of the AC [87,90,150]. The evoked firing rate is decreased in Shank3 +/− rats, VPA rats, and Fmr1 −/− rats, but increased in Mecp2 +/− and Cntnap2 -/− rats, Fmr1 −/− mice (particularly in layers 2/3), and Mecp2 overexpressing mice [28,30,32,33,117,123,146,152]. Interestingly, in vivo studies in VPA rats show no change in evoked firing rate to a simple 5-kHz tone, but decreased firing rates to human speech sounds, which fits with the patterns of evoked activity measured by fMRI in humans with autism [7,28,29,47].…”
Section: Electrophysiologymentioning
confidence: 89%
See 4 more Smart Citations
“…A higher frequency of mEPSPs than mIPSPs compared to WTs has been observed in A1 of VPA mice, Ehmt1 +/− mice and Pten conditional knockout mice, indicating underlying hypersensitivity of the AC [87,90,150]. The evoked firing rate is decreased in Shank3 +/− rats, VPA rats, and Fmr1 −/− rats, but increased in Mecp2 +/− and Cntnap2 -/− rats, Fmr1 −/− mice (particularly in layers 2/3), and Mecp2 overexpressing mice [28,30,32,33,117,123,146,152]. Interestingly, in vivo studies in VPA rats show no change in evoked firing rate to a simple 5-kHz tone, but decreased firing rates to human speech sounds, which fits with the patterns of evoked activity measured by fMRI in humans with autism [7,28,29,47].…”
Section: Electrophysiologymentioning
confidence: 89%
“…P2 Mixed results are also visible in the amplitude of the P2 peak, with awake mice again mostly showing increased or unchanged amplitudes [48,55,60,64,67,147]. Anaesthetised rats and mGluR5 −/− interneuron mice on a C57BL/6 background have decreased P2 amplitudes, with the exception of Cntnap2 −/− rats [8,28,30,31,123]. N2 and P3 amplitudes are not included in Table 2 as few studies reported them, but they were found to be decreased in anaesthetised rat Fmr1 −/− and Mecp2 +/− models, similarly to P2 [30,32].…”
Section: Cortical Event-related Potentialsmentioning
confidence: 96%
See 3 more Smart Citations